SPE International Heavy Oil Symposium 1995
DOI: 10.2118/30299-ms
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Upgrading of Heavy Oils by Low-Temperature Oxidation in the Presence of Caustic Additives

Abstract: The literature of the past thirty years shows that the low- temperature oxidation (LTO) of hydrocarbon liquids generally results in a more viscous end product. The In Situ Combustion Research Group at The University of Calgary has found, however, that upgrading can occur during LTO in the presence of caustic additives. Because it was believed that caustic inhibits oxidation reactions as evidenced by a reduction in or absence of coke formation, and allows the oil to upgrade by thermal cracking via a free radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…4 and Table 2) only 9°API crude oil and, no tetralin conversions. For the former run, the oil percentage of recovery was slightly smaller (1-2%) than that found in the upgrading process, which is consistent with the results reported by Shu et al [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and Kaskale and Farouq Ali 7 . However, a reduction from 0.8 to 3% in the percentage of tetralin conversion was observed in the Upgrading Process ( Table 2, run 3) in comparison with the bench scale experiments (run 1).…”
Section: Tetralin Naphthalenesupporting
confidence: 84%
See 2 more Smart Citations
“…4 and Table 2) only 9°API crude oil and, no tetralin conversions. For the former run, the oil percentage of recovery was slightly smaller (1-2%) than that found in the upgrading process, which is consistent with the results reported by Shu et al [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and Kaskale and Farouq Ali 7 . However, a reduction from 0.8 to 3% in the percentage of tetralin conversion was observed in the Upgrading Process ( Table 2, run 3) in comparison with the bench scale experiments (run 1).…”
Section: Tetralin Naphthalenesupporting
confidence: 84%
“…Several routes for underground crude oil upgrading have been reported. These concepts involve the following: Downhole steam distillation 1 , deasphalting [2][3][4][5] , underground visbreaking [6][7][8][9] , hydrogen [10][11][12][13][14][15][16][17] or hydrogen precursor injection [18][19][20][21][22] and in situ combustion [23][24][25] . With the exemption of the later route, the numerical simulation of downhole upgrading processes has been relatively less studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter (i.e., cold process) is used to improve the crude oil by dilution or destabilization, and deposition of the asphaltene components in the reservoir by injecting solvents that have a direct impact on viscosity reduction (Luo et al 2007b;Cavallaro et al 2005). The more frequently employed thermal techniques for heavy oil upgrading address breaking the heavier compounds of oil using combustion processes (Moore et al 1999;Cavallaro et al 2008), low-temperature oxidation (Xu et al 2000;Wichert et al 1995), aquathermolysis (Jiang et al 2005;Fan et al 2004;Maity et al 2010), and pyrolysis, also called thermal cracking or thermolysis (Speight 1970;Kumar et al 2011;Monin and Audibert 1988;Nassar et al 2013a). However, most of these techniques do not exceed 20 %-25 % oil recovery or 50 % for the steam-assisted gravity drainage (SAGD) process (Butler 1998;Nasr et al 2003;Hashemi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a number of researchers have conducted multiple studies about promoting the reservoir heat release and realizing reservoir spontaneous combustion at low temperatures. Wichert et al and He et al studied the effects of different metal particles and salts on the ISC process. Hamedi et al , and Rezaei et al found that nanoparticles could be used to promote thermal cracking at low temperatures and the stability of the combustion front propagation at high temperatures.…”
Section: Introductionmentioning
confidence: 99%